Microvascular Rarefaction and Heart Failure With Preserved Ejection Fraction - Zeng, Heng; Chen, Jian-Xiong (Frontiers in Cardiovascular Medicine, 2019)
Heart failure with preserved ejection fraction (HFpEF) is characterized by diastolic dysfunction and is commonly seen in the elderly and diabetic and hypertensive patients. Despite its rising prevalence, the pathophysiology of HFpEF is poorly understood and its optimal treatment remains undefined. Recent clinical studies indicate that coronary microvascular rarefaction (reduced myocardial capillary density) with reduced coronary flow reserve (CFR) is a major contributor to diastolic dysfunction in HFpEF patients. On a molecular level, endothelial cells (EC) are dependent on glycolysis for supporting their functions and vascular homeostasis. Sirtuin 3 (SIRT3) has a critical role in the regulation of endothelial glycolytic metabolism and thus affects angiogenesis. Disruption of SIRT3-mediated EC metabolism and impairment of angiogenesis may promote cardiomyocyte hypoxia and myocardial fibrosis, leading to diastolic dysfunction and HFpEF. This review summarizes current knowledge of SIRT3 in EC metabolism, coronary microvascular rarefaction and HFpEF.